PENGARUH PEMBERIAN SUSU KACANG HIJAU (VIGNA RADIATA) TERHADAP KETIDAKTERATURAN MENSTRUASI (OLIGOMENOREA) PADA MAHASISWI FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - SARI, NIKITA; ASFUR, ROBITAH (LP2MTBM MAKARIOZ, 2024)
Oligomenorrhea is a menstrual cycle that occurs longer than normal, which is more than 35 days. 7, 8 Factors that can lead to menstrual disorders include hormonal disorders, low BMI (Body Mass Index), nutritional status, and stress levels and other factors. stress can affect the production of the hormone cortisol which affects the female hormone estrogen.8 Mung beans are very beneficial for regularity because they normalize or balance the female hormone estrogen.13 The purpose of this study was to determine the effect of giving green milk (vigna radiata) to menstrual irregularities (oligomenorrhea). to students of the Faculty of Medicine, University of Muhammadiyah North Sumatra. This type of research is pre-experimental research using one group pretest and posttest. Based on this study, the research subjects used were medical architecture students at the University of Muhammadiyah North Sumatra who did not experience menstruation >35 days with the sampling technique of total sampling with a total of 15 samples. The results of 15 research subjects who were treated with 225 ml of mung bean milk and got an average value of 38.1 menstrual cycle pretest, and where the posttest in the first month got an average result of 30.6 days (31 days), in the posttest month the second 29.3 days (29 days), in the third month posttest 28.2 days (28 days). There is no effect of giving green milk to the menstrual cycle (oligomenorrhea) after treatment or at the pretest. There is a relationship between giving green milk to the menstrual cycle p = 0.000.